Uma análise conceitual da relação entre psique e corpo em Agostinho : os rudimentos do problema mente-corpo - Lima, Ricardo Pereira Santos (2015)
The aim of this thesis is (i) to demonstrate how Augustine understands and employs the concepts of body and mental life, so that then we would like (ii) to present some interpretative proposals concerning the relation between body and mental life (or psyche) in Augustine s tought. In the first section of this thesis, we will analyse the semantic-conceptual meanings of the Augustinian terminology to the many aspects of the human mental life. We will look over how Augustine employs and signifies the terms anima, animus, spiritus, mens, ratio, intellectus and intelligentia. In the second section, we will analyse the way that Augustine understands the human body, approaching theological, moral, ontological and anthropological aspects of this concept. In the third and last section, we will present three interpretative proposals that agree on how Augustine understands the psyche, the body, and their relationship. The two first proposals are very known and reputable by commentators (the substance dualism and the monistic idealism), whereas the third proposal represents our hypothesis and interpretative view, which is the psychosomatism. We conclude that, as from the way psyche, body and relationships are understood by Augustine, it is plausible to think of the mind-body relationships within the psychosomatic paradigm.